Oral anticoagulants controlled by the British comparative thromboplastin versus low-dose heparin in prophylaxis of deep vein thrombosis. Issue 6108 (4th February 1978) - Taberner, D A; Poller, L; Burslem, R W; Jones, J B
Abstract : The British comparative thromboplastin (BCT) was used to monitor the effectiveness of oral anticoagulants in preventing deep vein thrombosis (DVT) in patients undergoing major gynaecological surgery. All patients were screened for DVT with the use of the 125 I-fibrinogen scan. One hundred and forty-five patients aged 40 years or more were randomised into three groups. Group 1 received oral anticoagulant (nicoumalone) treatment, stabilised over five days before surgery and continuing into the second postoperative week. The other patients served as two contrast groups and were managed on a double-blind basis. Group 2 received a subcutaneous low-dose regimen of heparin calcium. Group 3 received subcutaneous saline. Eleven of 48 patients in the saline group, three of 49 patients in the heparin group, and three of 48 patients in the oral anticoagulant group developed DVT as judged by 125 I-fibrinogen scanning. The incidences in groups 1 and 2 were significantly lower than in the saline group. The falls in haemoglobin concentration and incidence of haemorrhage were similar in all three groups. The study showed that oral anticoagulant prophylaxis stabilised preoperatively and low-dose heparin were equally effective in preventing deep vein thrombosis in a moderate-risk group. Immediate preoperative prothrombin ratios of 2·0-2·5 and postoperative ratios of 2·0-4·0 with the BCT gave adequate protection without increased haemorrhagic risk.